Treatment Of Postpartum Anestrus Buffaloes With Controlled Internal Drug Releasing (Cidr) Device And Its Combinations - kumar, K. Senthil; Manokaran, S.; Mohan , B. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was conducted to know the effect of CIDR and it’s combinations with prostaglandin F2α (PGF2α) and gonadotrophin releasing hormone (GnRH) in postpartum anestrous buffaloes in terms of estrus signs, estrus induction rate and pregnancy rate. Thirty two healthy Graded Murrah buffaloes were selected after clinical, gynaecological and ultrasonographic examination and divided in to 4 groups comprising of 8 animals in each group viz. Group 1 (Control, not received any treatment), Group 2 (CIDR inserted intravaginally for 10 days), Group 3 (CIDR insert for 10 days plus 500 µg cloprostenol i/m on 9th day) and Group 4 (CIDR insert for 10 days, 500 µg cloprostenol i/m on 9th day and 10 µg of Busereline 24 hours after CIDR removal). The animals detected in estrus were bred through AI. The group 4 buffaloes exhibited estrus in 67.10 ± 12.5 hrs after CIDR removal with higher estrus induction (87.5%) and pregnancy rate (87.5%) than other groups.
Keywords: Buffalo; Postpartum anestrous; CIDR; PGF2α